The Effect of Harness Training Variations on the Speed of Spartan Athletic Club Jambi Sprint Athletes - Reno Reno; Sukendro Sukendro; Ahmad Muzaffar (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
The aim of this research was to determine the effect of variations in harness training on the speed of Jambi Spartan Athletic Club sprint athletes. This type of research includes research using a one-group pre-test-post-test design, namely the group that is given treatment. The sample was 3 male sprint athletes from the Jambi Spartan Athletic Club. Harness training is a type of training that uses weights when running. The goal of this exercise is to improve running ability and increase dynamic strength. These exercises can be performed at short or long distances, depending on the training goals. The ability of a person to cover a certain distance in a very short time is known as speed. Based on field data, the Jambi Spartan Athletic Club sprint athletes found that the pre-test data in the Shapiro-Wilk test was significant at 0.611, then the post-test data was significant at 0.628. Based on data from the results of the homogeneity test for the pre-test and post-test results for sprinter athletes at the Spartan Athletic Club, the number was significant at 0.983. Pre-test and post-test data have homogeneous variants or the data comes from populations with the same variance. Based on the results of the one-sample t-test showing this data, it can be seen that with the same number of samples in the pre-test and post-test data, a sig value <0.05 was found, which shows that there is an influence of variations in harness training on the running speed results of sprinter athletes at the Spartan Athletic Club. The magnitude of the difference between pre-test and post-test data is (5). The data obtained was concluded from the hypothesis or conjecture that Ha was accepted and Ho was rejected, because it showed that the pre-test and post-test were different. From the research results, it can be concluded that there is an influence of variations in harness training on the speed results of Spartan Athletic Club Jambi sprint athletes.